Assessment in textbooks: Exploring cognitive demand in first-year accounting textbooks - Ngwenya, J.C.; Arek-Bawa, O.O. (South African Journal of Higher Education, 2020)
The South African higher education program expects to develop graduates with high cognitive skills. This is endorsed further by the expectations of high cognitive attributes for entry level members from the Accounting professional bodies. Although learning is largely driven by assessment, relatively few studies have investigated assessments in Accounting textbooks. Furthermore, most used Bloom’s taxonomy as their sole analytical lens. Using a hybrid framework of Revised Bloom’s taxonomy and Leong’s levels of difficulty, this paper examines the cognitive demand of assessment tasks in selected level-one Financial Accounting textbooks used in South Africa and Kenya. The findings reveal the dominance of the Apply-Task-Hybrid and the possibility of enabling higher cognitive attributes within lower levels of cognition. The article provides new insight for accounting academics who seek to enhance their pedagogical engagement, as well as textbook producers, curriculum developers and professional accounting bodies. It also offers the Layered Analytical Framework as an alternative approach to examining cognitive demand across diverse fields of study, but specifically within the discipline of Accounting.